A Review of Forced Convection Heat Transfer Enhancement and Hydrodynamic Characteristics of a Nanofluid - K., Kadirgama; Hussein, Adnan M.; R. A., Bakar; Sharma, Korada Viswanatha (Elsevier, 2014)
The low thermal properties of liquids have led to investigations into additives of small size (less than 10 0 nm solid particles) to enhance their heat transfer properties and hydrodynamic fl ow. To summarise the experimental and numerical studies, this paper reviews these computational simulations and fi nds that most of them are in agreement with the results of experimental work . Many of the studies report enhancements in the heat transfer coeffi cient with an increase in the concentration of solid particles. Certain studies with a smaller particle size indicated an increase in the heat transfer enhancement when compared to values obtained with a larger size. Additionally, the effect of the shape of the fl ow area on the heat transfer enhancement has been explored by a number of studies. All of the studies showed a nominal increase in pressure drop. The signi fi cant applications in the engineering field explain why so many investigators have studied heat transfer with augmentation by a nanofl uid in the heat exchanger. This article presents a review of the heat transfer applications of nanofl uids to develop directions for future work . The high volume fraction of various nano fl uids will be useful in car radiators to enhance the heat transfer numerically and experimentally. Correlation equations can expose relationships between the Nusselt number, the Reynolds number, the concentration and the diameter of the nanoparticles. On the other hand, more work is needed to compare the shapes (e.g., circular, elliptical and fl at tube) that might enhance the heat transfer with a minimal pressure drop.